Green conversion of 5‐hydroxymethylfurfural to furan‐2,5‐dicarboxylic acid by heterogeneous expression of 5‐hydroxymethylfurfural oxidase in Pseudomonas putida S12 - Hsu, Chih‐Ting (Microb Biotechnol, 2020)
Transforming petrochemical processes into bioprocesses has become an important goal of sustainable development. The chemical synthesis of 2,5‐furandicarboxylic acid (FDCA) from 5‐hydroxymethylfurfural (HMF) is expensive and environmentally unfavourable. The study aims to investigate a whole‐cell biocatalyst for efficient biotransformation of HMF to FDCA. For the first time, a genetically engineered Pseudomonas putida S12 strain expressing 5‐hydroxymethylfurfural oxidase (HMFO) was developed for the biocatalytic conversion of HMF to FDCA. This whole‐cell biocatalyst produced 35.7 mM FDCA from 50 mM HMF in 24 h without notable inhibition. However, when the initial HMF concentration was elevated to 100 mM, remarkable inhibition on FDCA production was observed, resulting in a reduction of FDCA yield to 42%. We solve this substrate inhibition difficulty by increasing the inoculum density. Subsequently, we used a fed‐batch strategy by maintaining low HMF concentration in the culture to maximize the final FDCA titre. Using this approach, 545 mM of FDCA was accumulatively produced after 72 hs, which is the highest production rate per unit mass of cells to the best of our knowledge.